To solve the system of equations, we can use the method of substitution.
From the first equation, we have:
-x + 6y = 13
-x = 13 - 6y
x = -13 + 6y
Substituting this value of x into the second equation, we have:
4x - 10y = -10
4(-13 + 6y) - 10y = -10
-52 + 24y - 10y = -10
14y = 42
y = 3
Substituting the value of y back into the first equation, we have:
x = -13 + 6(3)
x = -13 + 18
x = 5
Therefore, the solution to the system of equations is (5, 3).
Solve the system of equations.%0D%0A–x+6y=13%0D%0A–%0D%0A%0D%0A+%0D%0A6%0D%0A%0D%0A=%0D%0A13%0D%0A%0D%0A4x–10y=–10%0D%0A4%0D%0A%0D%0A–%0D%0A10%0D%0A%0D%0A=%0D%0A–%0D%0A10%0D%0A(1 point)%0D%0A(, )
1 answer